The Influence of Olfactory Contexts on the Sequential Rating of Odor Pleasantness. (March 2017) - Nakano, Shiori; Ayabe-Kanamura, Saho
When we sequentially evaluate the characteristics of sensory stimuli, our evaluation of a current stimulus is influenced by those preceding it. One such effect is called hedonic contrast, whereby stimuli are rated more negatively (negative contrast) or positively (positive contrast) if they are preceded by more or less pleasant stimuli. The present study investigated the characteristics of hedonic contrast for olfaction and compared these characteristics with those of a more oft-studied modality, vision. The results from two experiments indicated that both positive and negative contrasts occurred in the sequential rating of picture pleasantness, whereas only negative contrast occurred for olfactory ratings. Notably, overrating of hedonically negative odors following a positive olfactory context was observed even when participants had already rated these same negative odors beforehand; conversely, this did not occur for positive contrast for either sense. These findings indicate that negative odors are more strongly influenced than positive ones, and the rating of positive stimuli may be adjusted to the preceding rating independent of stimulus context. The findings of this study revealed the unique characteristics of hedonic contrast for the olfactory senses.